ADDRESSING COVID-19 HEALTH DISPARITIES THROUGH VIRTUAL EDUCATION AND COLLABORATION. (20th December 2022) - Boyd, Kelly; Walker, Jacob; Benett, Jenil; Graupner, Jeffrey; Thompson, Katherine
Abstract: The South Side of Chicago, made up of predominantly Black and Latinx neighborhoods, has higher rates of COVID-19 infection and death rates and lower COVID-19 vaccination rates than other areas of Chicago. People aged 65 and older comprise nearly 15% of the region's population. The SHARE Network at the University of Chicago has a long history of providing healthy aging education to organizations serving older adults on Chicago's South Side. Using this pre-existing curricular structure, investigators created a monthly virtual workshop for community members to address COVID-19 related health disparities for older adults. Topics address aging concerns (i.e. dementia, mobility) and pandemic concerns (i.e. health disparities, vaccine hesitancy). At the end of the sessions, participants can ask questions to experts and share resources. Attendance has ranged from 15-20 participants, predominantly formal and informal caregivers. In post-attendance surveys, 80% of respondents identified as Black or African-American. Of the 20 respondents, 95% felt more knowledgeable about the topics discussed and all felt more knowledgeable about local health resources. Three-quarters felt more confident in the caregiving role, and 95% planned to make healthy lifestyle changes to benefit themselves or a loved one (i.e. more exercise, seeking respite care). These results demonstrate the positive impact of a timely community-informed virtual workshop. Providing virtual education on COVID-19 and healthy aging directly to older adult-focused community organizations and their clients is an early step health systems can take to address health disparities.